Co-management institution for sustainable inland fisheries management : a case study of the lower Songkhram River Basin, Thailand - Malasri Khumsri; Shivakoti, Ganesh P.; Gallardo, Wenresti G.; Kusakabe, Kyoko; Bhujel, Ram C.; Ministry of Agriculture and Cooperatives, Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The livelihoods and food security of many Thai people, especially those in the countryside, depend heavily on inland capture fisheries for animal protein, employment and income. Inland capture fisheries are characterized by a large diversity of fishing techniques, habitats, complex ecosystems with multiple species, and complex economic and social contexts. Nowadays, the sustainability of Thai inland capture fisheries is threatened by increasing fishing pressure and habitat degradation, largely as a result of population growth and an increased dependence on it. Current fisheries management in Thailand is considered incapable of controlling levels of exploitation and achieving an equitable sharing of resources. As a consequence, fisheries resources have been degraded and use conflicts have become a serious issue in terms of national development. Thus, the sustainable management of this fisheries sector is now a very important issue. Community based and co-management, whereby the state and a community of resources users jointly manage, is considered a possible way of addressing these issues, and has been promoted by the Thai government. However, co-management is hardly understood because of the multiple interests and government agencies who often participate. Hence their interaction is often extremely complicated. I assume in this study that co-management is a problem solving process, of negotiation and joint learning resulting in problem-solving, rather than a fixed state. Successful development of fisheries co-management depends on its design, how it is implemented, and its context. It needs to be clearly understood how different management tasks are organized and distributed, focusing on the function rather than on the formal structure of the system. The study was conductedto provide an alternative understanding of co-management for inland capture fisheries, as an adaptive management approach. Using an institutional analysis approach, the current performance of co-management for the Lower Songkhram River Basin fisheries was assessed by analyzing the linkage among the variables of resources, community and institution attributes of a fishery system, to identify and examine the key factors affecting the organization and outcomes of inland capture fisheries co-management. Various rapid and participatory assessment tools and in-depth interviews of fisher household were used in data collection. The capture inland fishery system in the LSRB is a typical large river basin characterized by various species-rich ecologically assemblages, in which population dynamics are difficult to examine and predict. This complexity is currently expressed in the diversity and variability of the fishing techniques used. The fisheries resources are currently managed under complex multiple property rights regimes, through both national and local institutions. The clearly manifested problems associated with capture fisheries are an increased rate of fisheries resources degradation, the use of illegal fishing gear, and conflicts in resources use. Solving these problems from the perspectives of all stakeholders is requested by both government and local communities. The study found that the performance and sustainability of current co-management for inland capture fisheries are constrained by a lack of clearly defined property rights and specific rules aimed at sustainable resources use, a mismatch between local and state institutional arrangement for fisheries management, and a lack of enabling legislation. To improve fisheries management in the LSRB, co-management should be continued, but refocused on a consideration of the ownership of rights in decision making about the use and management of resources, rather than on the ownership of the resource. Moreover, to achieve a more effective property rights system, legitimizing local rights, local authority, roles, and ivmanagement structures should be specified clearly in policy guidelines. The national laws should encourage local people{u2019}s rights in management. Therefore, the Thai cabinet must consider and quickly promulgate a new Fisheries Law. Further, specific rules must be set up by fishers and government agencies to ensure sustainable fisheries resources use, especially for the control of destructive gears. Finally, external threats to fisheries resources, especially intensive agriculture and dam development, need to be addressed if sustainability is to be improved.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2008
Keywords: Fishery management -- Thailand -- Songkhram River Basin